Populism and Socio-Political Transformation in Latin America - Munck, Ronaldo (Revista de Estudios Globales. Análisis Histórico y Cambio Social, 2024)
Through the concept of «populism» Ronaldo Munck offers a series of approaches to the various methodological and theoretical perspectives that have studied it for decades. The article highlights both the complexity of this concept and its ambiguity.